Peran Dakwah Jamaah Hadrah Hubbun Nabi Dalam Meningkatkan Semangat Aktivitas Keagaman Remaja Desa Tanjungan Kecamatan Driyorejo Kabupaten Gresik - Suparno, Suparno (LPPM, 2019)
Islam is a religion of da'wah, meaning religion that always encourages its adherents to always active Islamic teachings. Even the advanced pullback of Muslims relies heavily on the da'wah activities it does. Da'wah can be done by means of Bill-oral, Bil Qalam, bil of things and can go through various forums as long as its purpose is to invite to live the command of Allah SWT in the form of faith and exempvises his apostles. Through Da'wah which is filled with Dhikrullah, praise the Prophet Muhammad with the accompaniment of the music that will captivate the society especially the youth follow the religious activities carried out by the congregation Sulthan. From the background, there will be a desire from researchers to know the extent of the role of the propagation of the Congregation of the Hubbun Prophet in increasing the spirit of the activity of youth religious activities village of Driyorejo District of Gresik Regency. And what are the encouraging factors in increasing the spirit of the youth's religious activities. This research uses qualitative descriptive research. Data collection using observations, interviews, and documentation. Through interviews and observations it is known that the main subjects studied were the youth members of the Hubbun prophet. The results showed that the mosque returned to life with all the religious activities and the taxon of youth by the worshippers of the Prophet Hubbun. This activity is done by preaching the congregation is a dhikr, shalawat with the suffix Sulthan rebana, Tahlil, Ad-Diba'i, Yellow Book and others. With the dhikr and Shalawat the youth will feel calm in their souls so that they can think clearly and do good things. And through the Mauidzah Hasanah and good guidance can affect the morality and the lives of the youth who follow the congregation of the Sulthan. The spirit, cooperation, feeling of sincerity and high sacrifice from the managers in spending time for the activities of the congregation and the community who are conducive to make the activities of the Congregation of the Prophet Hubbun can run well. Keywords: da'wah, Hadrah, religious activity.